Multilingualism as a Phenomenon of Public Broadcasting (Macedonian Holding MRT) - D. A. Sorokin (Научный диалог, 2023)
The article focuses on the study of public broadcasting in the Republic of North Macedonia. The key structure of public broadcasting is the representation of civil society. Despite the abundance of scientific literature on this topic, there is still research interest in identifying the characteristics of different public broadcasting systems. The article analyzes the activities of the Macedonian Holding MRT, which produces television and radio content. The results of monitoring the informational and non-informational broadcasting of MRT channels (including educational and entertainment components) are presented in the article. Through content analysis of the broadcasting schedule, the specific activities of MRT are determined: the public broadcaster of North Macedonia broadcasts television and radio programs in 9 languages for all ethnic groups represented in the country. The author concludes that multilingualism gives MRT a certain exclusivity, and ethnic minorities are provided with the opportunity not only to consume television and radio content in their native language but also to be represented in the multiethnic Macedonian society.